Pragmatic Analysis Of Anger Expressions On "An Enemy Of The People" Manuscript By Henrik Ibsen - Wikandari, Shinta Dewi; , Dra. Malikatul Laila, M. Hum; , Dra. Siti Zuhriah Ariatmi, M.Hum (2015)
This research belongs to decsriptive qualitative research. The research purposes are to describe the causes of anger expression that appear and to explain the differences of anger expression in stress, intonation, dirty word, irony and direct expression between a man and a woman, old woman and young woman, and politicians and scientists on "An Enemy of the People" manuscript by Hendrik Ibsen. The data of this research is the expression of anger in the forms of words, sentences and information related to anger expression on "An Enemy of the People" manuscript by Henrik Ibsen. The data sources of this research are "An Enemy of the People" manuscript by Henrik Ibsen. The researcher used observation and documentation as the method of collecting data. The results of the research show that: First, There are eight causes of anger expression that appear in "An Enemy of the People" manuscript. There are: (1) 1 datum or 1,04% belongs to being treated unfairly and feeling powerless to change it condition; (2) 1 datum or 1,04% belongs to losing out when money is at stake; (3) 1 datum or 1,04% belongs to being interrupted when pursuing a goal; (4) 5 data or 5,21% belongs to being verbally or physically assaulted; (5) 10 data or 10,42% belongs to facing a threat to the selves or the loved ones; (6) 16 data or 16,67% belongs to suffering a blow to the participant or the place within a social group ; (7) 30 data or 31,25% belongs to someone going against a principle that the people consider important; and (8) 32 data or 33,33% belongs to feeling disappointed by someone else or in the selves. Second, a man and a woman, old woman and young woman, and politicians and scientists expresses the anger on "An Enemy of the People" manuscript, used: (1) stress; (2) intonation; (3) dirty word; (4) irony; and (5) direct expression. a) A man expresses his anger using stress, high intonation, dirty word, irony and direct expression more than a woman. b) An old woman expresses her anger using stress, high intonation, dirty word, irony and direct expression more than an old woman. c) Politicians expresses his anger stress, high intonation, dirty word, irony and direct expression more than politicians.